Cuidados de enfermería en pacientes con abordaje de vía aérea en una unidad de cuidados intensivos - Jiménez Bonilla, Joselyn Estefanía (2025)
Effective management of respiratory ventilation plays a vital role in the care of patients with pulmonary disorders and is considered a fundamental pillar of care for severely ill patients requiring admission to an intensive care unit. The aim of this article was to identify the nursing care provided to patients undergoing airway access in an intensive care unit, through a bibliographic review. This was a qualitative, non-experimental, descriptive and documentary study. Databases were consulted, identifying 169 publications. By applying the Preferred Reporting Items for Systematic reviews and Meta-Analyses method, or PRISMA method, a set of 16 publications was obtained, which were incorporated into the review. The results reveal that nursing care provided to patients with airway access in the intensive care unit is effective in the following areas: healthcare, by promoting an increase in the quality of care; epidemiological, by favouring a reduction in morbidity and mortality rates and a decrease in hospital stay; and economic, because it allows to mitigate health costs. In conclusion, nursing care directed to patients in the intensive care unit with airway management can be classified into 5 domains: care aimed at (1) verifying the patient's condition (hemodynamic and neurological status), (2) promoting appropriate gas exchange, (3) care of the endotracheal tube or tracheostomy, (4) hygiene and positioning measures and (5) communication.